Of being a Malay - Abd Razak, Dzulkifli (2007)
THE deputy prime minister was quoted as saying: "The Malay mind must, therefore, be driven towards learning and training in positive, creative, lateral, proactive and innovative thinking. "The most important investment that a Malay family can make is not the procurement of land, property or fancy cars, but in their children's education." Perhaps at this juncture, it is useful to recall an old Malay saying: Orang tuatua berkata, jika ada wang beli emas. Jual emas, beli berlian, jual berlian beli manikam. Jual manikam, beli ilmu.